SYNTHESIS AND CHARACTERIZATION OF POLY(ε-CAPROLACTONE)-POLY(ETHYLENE GLYCOL)-POLY(ε-CAPROLACTONE) COPOLYMERS: INVESTIGATION OF THE EFFECT OF BLOCKS ON MICELLIZATION - Gokce Kocabay, Ozlem; Ismail, Osman (EDITURA ACAD ROMANE, 2018)
Poly(epsilon-caprolactone)-poly(ethylene glycol)-poly(epsilon-caprolactone) copolymers are important synthetic biomedical materials with amphiphilicity, controlled biodegradability and great biocompatibility. This work reports synthesis and characterization of Poly(epsilon-caprolactone)-poly(ethylene glycol)-poly(epsilon-caprolactone) triblock copolymers for drug delivery. Triblock copolymers were synthesized by ring-opening polymerization. Molecular weight of used poly(ethylene glycol) is 1450, 3350 and 12000 g/mol and weight ratios of epsilon-caprolactone / poly(ethylene glycol) are 0.5, 1, 2, 24. Synthesis of triblock copolymers was confirmed by H-1-NMR and triblock copolymer micelle formation was studied by fluorescent technique. According to the H-1-NMR spectra peaks at 1.42, 1.62, 2.34, and 4.09 ppm are assigned to methylene protons of - (CH2)(3)-, -OCCH2-, and -CH2OOC- in poly(epsilon-caprolactone) units, respectively. The sharp single peak at 3.66 ppm is attributed to the methylene protons of homosequences of the poly(ethylene glycol) oxyethylene units. The critical micelle concentrations of the polymers were in the range of 0.000293-0.019202 mg/mL indicating an excellent dynamic stability.
Keywords: biodegradable; PCL-PEG-PCL; critical micellization concentration; amphiphilic copolymer micelles; POLYMERIC MICELLES; TRIBLOCK COPOLYMERS; DOXORUBICIN DELIVERY; SUSTAINED-RELEASE; WATER; NANOPARTICLES; CHITOSAN; GLYCOL); PYRENE; PROBE; Chemistry